2015
DOI: 10.1111/fare.12098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Pressure on Parent Positivity, Parenting, and Adolescent Positivity into Emerging Adulthood

Abstract: The current study describes how positivity can be incorporated into the Family Stress Model to explain resilience to disrupted family processes in the face of economic distress. Prospective, longitudinal data came from 451 mothers, fathers, and youth participating from their adolescence through early adulthood. Assessments included observational and self-report measures. Information regarding economic pressure, parental positivity, and parenting were collected during early adolescence, positivity was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 41 publications
7
44
2
4
Order By: Relevance
“…For example, strategies to improve parent psychological wellbeing, couple relationships, or parenting practices during times of stress (Walsh, 2012) may be helpful in preventing negative consequences for children. Indeed, parenting that is high in warmth and effective communication has been associated with child positive outcomes even for families facing economic disparity (Neppl, Jeon, Schofield, & Donnellan, 2015). By increasing supportive family interactions, such intervention efforts may help foster long lasting positive developmental outcomes for children exposed to economic hardship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, strategies to improve parent psychological wellbeing, couple relationships, or parenting practices during times of stress (Walsh, 2012) may be helpful in preventing negative consequences for children. Indeed, parenting that is high in warmth and effective communication has been associated with child positive outcomes even for families facing economic disparity (Neppl, Jeon, Schofield, & Donnellan, 2015). By increasing supportive family interactions, such intervention efforts may help foster long lasting positive developmental outcomes for children exposed to economic hardship.…”
Section: Discussionmentioning
confidence: 99%
“…Caprara et al (2009) demonstrated that these positive attributes may be explained by both genetic factors and the environment. Recently, Neppl, Jeon, Schofield, and Donnellan (2015) evaluated how parental positivity can be incorporated into the FSM to explain resilience to disrupted family processes in the face of economic distress. They concluded that personal characteristics linked to a positive outlook may foster nurturant parenting, even in times of economic strain.…”
mentioning
confidence: 99%
“…La pérdida del empleo supone una disminución de los ingresos en el hogar, con consecuencias que van más allá de la disminución del poder adquisitivo de la familia. Se ha visto que la disminución -y especialmente la desaparición-de los ingresos, perjudica a la salud mental de los individuos desempleados (Buendía, 2010;Creed y Macintyre, 2001;Janlert y Hammarstrom, 2009; Nuttman-Swartz y Gadot, 2012;) y a las relaciones familiares (Conger et al, 2010;Mistry et al, 2008;Vinokur et al, 1996;Weckström, 2012) , afecta a la capacidad de las familias para satisfacer las necesidades más básicas de sus miembros (Neppl, et al, 2015;Wray, 2015) y dificulta el acceso a la formación académica (Kalil y Wightman, 2011), contribuyendo así a la transmisión intergeneracional de la desigualdad y la pobreza (Flores et al, 2016).…”
Section: Vulnerabilidad Y Desempleounclassified